Increasing the Competitiveness of Vocational Schools in 4C Skills-Based Programs through SWOT Analysis - Izuddin Syarif; Agus Timan; Sultoni Sultoni (Universitas Sultan Ageng Tirtayasa, 2023)
4C Skills which are 21st century competencies including critical thinking, creative thinking, collaboration and communication are important skills in vocational school graduates. The purpose of the research is to analyze the internal and external factors relevant to improving 4C skills and owned by SMKN 1 Paringin using SWOT analysis. This research method is qualitative with case study type. The research location is SMKN 1 Paringin, Balangan Regency, South Kalimantan Province. The data collection techniques used were in-depth interviews, observation, and documentation. There were 19 informants ranging from school leaders, heads of expertise programs, and productive teachers to students. Stages of data analysis were carried out starting from data condensation, data display to conclusion drawing verification. The IE Matrix score is calculated based on the rating of sub-factors that are relevant to improving 4C skills. The results showed that the school has the opportunity to grow and develop with the IE Matrix score in quadrant I. The recommended strategy is the development of community projects for students. The proposed strategy is the application of student competencies and the results of scientific writing competitions in the form of control system products through community projects for underprivileged communities, in partnership with the village government. Development of a school bulletin through a student journalism program in partnership with local newspaper journalists as mentors and reviewers. Another strategy is the development of a Production Unit through a teaching factory in the form of services for the surrounding community in partnership with partner industries and school alumni. The final results of all programs must still be evaluated and included in the student soft skills assessment system.